Characterization of Innate Immune Responses to House Dust Mite Allergens: Pitfalls and Limitations - Jacquet, Alain (Frontiers in Allergy, 2021)
Whereas House dust mite (HDM) allergy results from a dysregulated Th2-biased adaptive immune response, activation of innate immune signaling pathways is a critical prerequisite for the initiation of HDM sensitizations. Such innate sensing is mainly controlled by the airway epithelium and the skin. The resulting release of epithelial-derived proinflammatory cytokines and innate alarmins such as GM-CSF, IL-25, IL-33 and TSLP mediates the activation of ILC2 cells and cDCs to promote Th2-biased inflammation. Significant progress in the elucidation of HDM innate immune activation has been made in the past decade and highlighted key roles of the LPS/TLR4 axis, chitin-dependent pathways together with HDM protease allergens. However, the precise mechanisms by which HDM allergens are sensed by the innate immune system remain largely unknown. Such investigations are made difficult for several reasons. Among these are 1)the natural association of HDM allergens with immunostimulators from the mite exoskeleton as well as from environmental microorganisms/pollutants or endosymbiotic bacteria; 2) the purification of individual HDM allergens from extracts in sufficient amounts and devoid of any microbial and protein impurities; 3) the production of correctly folded recombinant HDM allergens which could display the same biological activity than their natural counterparts; 4) Accessibility to human epithelial samples with cellular heterogeneities and inter-donor variations; 5) Translation of experimental data from mouse models to humans is almost missing. The goal of the present mini-review is to emphasize some important limitations and pitfalls in the elucidation of innate immunostimulatory properties of HDM allergens.